TRANSFORMING GEOLOGICAL AND LANDISLIDE SUSCEPTIBILITY MAPPING DATA TO LINKED (OPEN) DATA FOR HAZARD MANAGEMENT - Atzemoglou, A.; Kotzinos, D.; Grinias, El.; Spanou, N.; Pappas, Ch. (Bulletin of the Geological Society of Greece, 2016)
The frequent lack of information to populations exposed to landslides is a component of the social vulnerability and can strongly increase the risk on lives and infrastructures. Determining the extent of the landslide hazard requires identifying those areas which could be affected by a damaging landslide. The users need to integrate different landslide data in order to first understand and then possibly become resilient to any potential catastrophic event. More precisely, public and private organizations can choose between different land use options to minimize the risk on the already existing infrastructures or to reduce the hazard itself through mitigation measures. From the other hand, the land use planners can also take best decisions before planning new infrastructures in high risk landslides’ areas. Based on these data we have also implemented new tools, available every day and reusable by anyone interested, to identify land areas susceptible for landslides. The tools are based on cloud web services, especially for the management and presentation of these datasets in order to provide stakeholders with valuable information about past distribution of the landslides, type of bed rock, rainfall etc. in order to focus on land use policies and assess an impending landslide.